Modulating the nutritional composition of green onion (Allium cepa L.) through strategic sowing time management in tropical agroecosystems - Manasranjan, P; Bibhuti, B S; Pradyumna, T; Barsha, R P; Adyasha, D; Mala, D P; Soumya, P M; Nityamanjari, M; Tapas, P; Bhabani, S N (Plant Science Today, 2026)
A field experiment was conducted at the Regional Research and Technology Transfer Station, Bhawanipatna, Odisha, India, to determine the best sowing time for green onion production and quality. The study used a Randomised Block Design with five sowing dates at 15-day intervals, from 15th June to 15th August, 2023 and replicated four times. The onion variety Bhima Dark Red performed best when sown on 15th August (D5), during the late kharif season. This late-sown crop showed significant improvements in growth, including taller plants (57.57 cm), more leaves per plant (7.28), longer leaves (46.38 cm), thicker leaves (0.71 cm) and superior fresh (3.49 g) and dry weight (0.36 g) of leaves. Additionally, the late-sown green onion had better phytonutrients with higher chlorophyll content (62.24 SPAD units), reducing sugar (2.50 %) and total sugar (2.96 %). Onion leaves had the highest potash (2.38 %) and sulfur (0.58 %) content. However, non-reducing sugars, ascorbic acid, soluble protein, crude protein, nitrogen and phosphorus levels were lower in these leaves. Correlation studies on bioactive components at 90 days after planting showed positive relations between chlorophyll, sugars and potash, as well as between crude protein and nitrogen. Inverse relationships appeared between sugars and protein and between chlorophyll and ascorbic acid. Principal component analysis indicated strong positive associations among photothermal units, growing degree days and ascorbic acid, suggesting that 15th August was the best sowing date for maximising nutritious leaves. These results highlight the value of green onions planted on 15th August as a rich source of phytonutrients and the importance of choosing the right sowing dates for better yield and nutrition.